The Influence of the Use of Instagram Info Garut Media on the Trust of Garut University Students - Sani Rahman; Ridwan Mustopa; Hanifa Addawiah; Detya Wiryany (Indonesian Scientific Publication, 2026)
The rapid development of digital technology has transformed patterns of information access through visual-based platforms such as Instagram. Although Indonesia has approximately 191 million social media users, public trust in news distributed via social media remains relatively low, at only 39%. In this context, the @infogarut Instagram account has emerged as an important local information source for Garut University students, contributing 67.5% to their daily information needs. This study aims to examine the influence of @infogarut Instagram usage on students’ trust in digital information. Using a descriptive quantitative approach, data were collected from 32 Garut University students through a closed-ended questionnaire with a five-point Likert scale, selected via purposive sampling. Instagram usage was measured through indicators of access intensity, feature utilization, and user interaction, while trust in digital information was operationalized through three dimensions: information ethics, transparency, and content objectivity. Data analysis involved validity and reliability testing followed by simple linear regression using SPSS. The results show that Instagram usage (mean score 3.70) and trust in digital information (mean score 4.11) are both categorized as good, and that increased frequency, duration of access, and interactive engagement with @infogarut content have a positive and significant effect on students’ trust formation. These findings indicate that ethical information practices, transparency, and objective content management play a crucial role in enhancing public trust in local digital media. The novelty of this research lies in its focus on district-level digital media and in its substantive operationalization of trust indicators that are highly relevant to local public information governance.